VD_FINDINFO Pron / 2012 / 122 vom 30. Mai 2012 - VD Tribunal cantonal (2012)
PROCÈS DEVENU SANS OBJET, PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE, MESURE PROVISIONNELLE | 397a CC, 398b CPC, 398d CPC